PENDIDIKAN KECAKAPAN HIDUP DALAMBINGKAI MORAL SEBAGAI STRATEGI BROAD BASED EDUCATION - Saefur Rochmat (Jurnal Cakrawala Pendidikan, 2005)
Up to now, our educational system have not succeeded in increasing the quality ofmanpower, in which we are in the 132"" intheworId, one level below Vietnam, a nation which is just out ofthe internal dissent. It happens because Indonesia follows the educational system oftM West minus its cultural aspect. The impacts will be more disaster ifthe educational process only emphasis onthe cognitive aspect ofit, moreover ifit is reduced into the memory aspect. Ifwe give Broad Based Education (BBE) the meaningful, it will beable to overcome some disabilities ofoureducational system. The BBEprograms launching together with the policy ofthe Local Autonomy give all districts the opportunities to set up their educational system regionally in accordance with their culture. Educational system should relevant to their philosophical, as the system ofknowledge oftheir societies, which consist ofall symbols with their concepts ofepistemology to integrate the process ofmodernization into a coherent system. Ifthe educational system is given the appropriate cloth in accordance with the culture ofthe nation it will run well, besides as an alternative to the secular education ofthe West which is not able to produce the wisdom. We can take all the theories and concepts ofthe West to be applied into the situation and conditien in Indonesia so that the results'Ofeducation are useful to cope all problems which exist in our societies. We should also lead education process up to the evaluation level in accordance with the culture and morality ofour nation